Pictorial information about subclinical atherosclerosis reduces the CVD risk: Results from the VIPVIZA RCT. (11th May 2021) - Bengtsson, A; Norberg, M; Ng, N; Carlberg, B; Gronlund, C; Hultdin, J; Lindahl, B; Lindahl, B; Nordin, S; Nyman, E; Wennberg, P; Wester, P; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Public Institution(s). Main funding source(s): Region Västerbotten and the Swedish Research Council Background: The VIPVIZA trial has previously shown beneficial effects on cardiovascular disease (CVD) risk scores 1 year after sending pictorial information of carotid ultrasound imaging (Picture 1) to individuals and their physicians Purpose: To investigate whether the beneficial effects on CVD-risk observed at 1-year were sustained over three years  Methods: VIPVIZA is a pragmatic prospective open-label randomized controlled trial with blinded evaluators performed within a CVD prevention programme integrated in the regular primary health care in Västerbotten County, Sweden. Individuals aged 40, 50 or 60 years old with one CVD risk factor were enrolled and randomised 1:1 to intervention (n = 1749, pictorial information about subclinical atherosclerosis provided to participants and physicians, Picture 1) or control group(n = 1783, no information to participants or physicians). Intervention participants also recieved a follow-up phone call and the corresponding physicians written guideline-based information about the clinical significance of carotid ultrasound results. Participants were examined at baseline (2013-2016), after one and at three years Results: A significant beneficial effect on cardiovascular risk was observed at the 3-year follow-up; Framingham Risk Score (FRS) was 13.38 for the intervention group and 14.08 for the control group(p = 0.047) and SCORE was 1.69 vs. 1.82(p = 0.022) respectively. The 3-year results adjusted for sex and educational level showed significant differences between the intervention and control group in FRS, SCORE, P-Total-Cholesterol, P-LDL-Cholesterol and waist circumference in favour of the intervention group. Analysis by sex showed difference in differences(DID) in FRS for men -1.19(95% CI -2.01 to -0.37) and -0.50(95% CI -0.93 to -0.07) for women and in SCORE for men -0.20(95% CI -0.33 to -0.06) and -0.08 (95% CI -0.13 to -0.04) for women, between the two groups over 3 years. Similarly, there were significant differences in DID in all educational groups. Further stratification by baseline FRS and SCORE risk category, showed a beneficial pattern of the intervention in all risk groups, however the DID at the 3-year follow-up was statistically significant only in the intermediate risk group for both FRS -1.34(95% CI -2.13 to -0.56) and SCORE -0.19(95% CI -0.32 to -0.05) Conclusions: This study provides evidence of sustained effects over three years of pictorial information of subclinical carotid atherosclerosis on the reduction of cardiovascular risk regardless of sex and educational level. Importantly, a statistically significant intervention effect was seen in the intermediate risk group, where the majority of CVD events occur. Visualization of subclinical atherosclerosis may be one way to approach individuals at intermediate risk of CVD, a group where sufficient prevention is often overlooked. However, further studies are needed to investigate the intervention effect on hard end points as CVD-events and death.